2002
DOI: 10.1080/080352502320764193
|View full text |Cite
|
Sign up to set email alerts
|

Enteral administration of hematopoietic growth factors in the neonatal intensive care unit

Abstract: Calhoun DA. Enteral administration of hematopoietic growth factors in the neonatal intensive care unit. Acta Paediatr 2002; Suppl 438: 43-53. Stockholm. ISSN 0803-5326 By 20 wk of gestation, the human fetal gastrointestinal (GI) tract morphologically resembles that of the term infant, but functional development is limited before 26 wk. By 30 wk of gestation, the fetus has the capacity for limited digestion and enteral absorption. GI growth and development continue postnatally. Trophic factors, including nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…95 We know from other studies that trophic factors in amniotic fluid bathing the fetal intestine during the third trimester of pregnancy are needed to produce a profound maturational effect on the intestine's ability to appropriately respond to colonizing bacteria. 96 For example, mature enterocytes interacting with colonizing bacteria can distinguish between commensal bacteria and potential pathogens. The enterocyte responds to pathogen interaction with a selflimited inflammatory response to prevent penetration, leading to gastroenteritis or sepsis.…”
Section: Necmentioning
confidence: 99%
“…95 We know from other studies that trophic factors in amniotic fluid bathing the fetal intestine during the third trimester of pregnancy are needed to produce a profound maturational effect on the intestine's ability to appropriately respond to colonizing bacteria. 96 For example, mature enterocytes interacting with colonizing bacteria can distinguish between commensal bacteria and potential pathogens. The enterocyte responds to pathogen interaction with a selflimited inflammatory response to prevent penetration, leading to gastroenteritis or sepsis.…”
Section: Necmentioning
confidence: 99%
“…Amniotic fluid contains intestinal growth factors that, when swallowed by the fetus, bind to receptors on the luminal surface of villous enterocytes. 3,4 We postulated that it is the lack of such binding that results in the dysmorphic mucosa we observed 2 and that a limitation in amniotic fluid swallowing could constitute at least part of the explanation for postoperative feeding intolerance.…”
Section: Introductionmentioning
confidence: 80%
“…It was once thought that the critical factor was the volume of liquid swallowed, but experimentation showed that it is the growth factors in amniotic fluid that are critical to small bowel villous development. 4,12 Amniotic fluid contains multiple intestinal growth factors that have cognate receptors on the luminal surface of developing villous enterocytes. 3,4,12 The precise action of each factor remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations